2021
DOI: 10.3389/fmats.2021.683851
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anomalous Dynamic Responses of Fiber Metal Laminates Under Pulse Loading

Abstract: Composed of metallic layers and composite plies, fiber metal laminates (FMLs) combine inherent advantages of metals and composites. The phenomenon of anomalous response behavior, in which the permanent deformation is in the opposite direction to the incoming pressure wave, has been discovered in dynamic responses of monolithic plate subjected to impulsive loading. In this study, dynamic responses of FML plates of various configurations are examined and compared against the responses of a monolithic plate using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It was shown that FMLs with 0.3 wt% GnPs logged the best impact performance. Zhai et al [13] examined the dynamic responses of FMLs with various configurations using finite element analysis. It was found that the thickness of the laminate significantly affected the final deflection, which mainly depended on the configuration and specification of FMLs.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that FMLs with 0.3 wt% GnPs logged the best impact performance. Zhai et al [13] examined the dynamic responses of FMLs with various configurations using finite element analysis. It was found that the thickness of the laminate significantly affected the final deflection, which mainly depended on the configuration and specification of FMLs.…”
Section: Introductionmentioning
confidence: 99%